Knowledge sharing among scientists : A causal configuration analysis - Oliveira, Mirian (2022)
Scientists are professionals who create knowledge, and academia is a place for creating and sharing knowledge. In this study, we examine the causal configurations that identify particular patterns that lead to knowledge sharing among scientists. Our examination uses a fuzzy-set qualitative comparative analysis. The data come from an online survey of 620 scientists in top Portuguese research centers in engineering, technology, health sciences, social sciences, and the arts and humanities. The results show that being a research team leader is an important condition for knowledge sharing. Productive scientists tend to share their knowledge, whereas unproductive ones tend not to share. The fear of losing power due to knowledge sharing restrains its use, while the scientists who are not afraid share their knowledge. The results do not identify the contribution of senior scientists. This finding indicates older or more experienced scientists are not related to the phenomena.